A dynamic population of weedy rye - Suneson, C.A.; Rachie, K.O.; Khush, G.S. (Wiley, 1969)
Natural establishment and spread of a diverse and heterotic weedy rye population in California's northern mountain counties is reported. The dramatic take‐over by this interspecific derived population can be ascribed to a favorable climate and soil, and an unusual opportunity for continued introgression with diverse cultivars of rye.We encourage further study of this example of genetic introgression under conditions of natural selection. Information may be applicable to rye breeding, new species (Triticale) production, and population genetics. Its potential as a weed must also be considered.